Preceding child survival status and its effect on infant and child mortality in India: An evidence from National Family Health Survey 2015-16 - Shobhit Srivastava; Shubhranshu Kumar Upadhyay; Shekhar Chauhan; Manoj Alagarajan (BMC, 2021)
Abstract Background India has achieved impressive gains in child survival over the last two decades; however, it was not successful in attaining MDG 2015 goals. The study's objective is to inquire how the survival status of the preceding child affects the survival of the next born child. Methods This is a retrospective analysis of data from the National Family Health Survey, 2015-16. Analysis was restricted to women with second or higher-order births because women with first-order births do not have a preceding child. Proportional hazards regression, also called the Cox regression model, has been used to carry out the analysis. Kaplan-Meier (K-M) survival curves were also generated, with a focus on preceding birth intervals. Results Results found that female children were more likely to experience infant mortality than their male counterparts. Children born after birth intervals of 36+ months were least likely to experience infant mortality. Mother's education and household wealth are two strong predictors of child survival, while the place of residence and caste did not show any effect in the Cox proportional model. Infant and child deaths are highly clustered among those mothers whose earlier child is dead. Conclusion Maternal childbearing age is still low in India, and it poses a high risk of infant and child death. Education is a way out, and there is a need to focus on girl's education. The government shall also focus on raising awareness of the importance of spacing between two successive births. There is also a need to create a better health infrastructure catering to the needs of rich and poor people alike.